Malaysia's Socio-Economic Transformation : Ideas for the Next Decade - Basu Das, Sanchita; Lee, Poh Onn (Book collections on Project MUSE., 2014)
Since 1957, Malaysiaâ€TMs economic development has been an account of growth, transformation, and of structural change. More than 75 per cent of its gross domestic product (GDP) comes from the manufacturing and services sectors. However, Malaysia is stuck in a middle-income trap and is facing challenges on the economic and political front. In June 2010, Prime Minister Najib Razak unveiled the 10th Malaysian Plan (2011-15) to chart the development of Malaysia from a middle- to high-income nation ...